Threats to professional dignity of Iranian clinical nurses: A qualitative study - Ali Abbasi; Alice Khachian; Abbas Ebadi; Hosein Bagheri (Wiley, 2023)
Abstract Aim Identifying threats to the nurses' professional dignity has an important role in maintaining and promoting their dignity. This study aimed to evaluate the perception of Iranian nurses' experiences of threats to their professional dignity in clinical settings. Design A qualitative directed content analysis approach was used. Methods The present qualitative study was conducted in Iran.Clinical nurses were selected using the purposive sampling method. Data were collected through in‐depth semi‐structured interviews with 15 clinical nurses from October 2020 to March 2021. The qualitative content analysis method was used to analyze the data. Results Two main categories and 16 subcategories were extracted as follows: (1) professional factors (containing seven subcategories) and (2) organizational factors (containing nine subcategories). Conclusions To promote the professional dignity of nurses, it is recommended to identify the factors threatening their professional dignity and create healthy work environments for them.